Learning Models To Increase Learning Motivation Through The Application Of Bandlab - Hery Budiawan Budiawan; Siti Pujawati Nurmalasari (Universitas Negeri Semarang, 2022)
The purpose of this study is to determine whether there is a difference in the level of student learning motivation between classes and the use of application-based learning media, namely bandlabs with classes without the use of bandlab learning media at SMPN 24 Jakarta. And the second is the supporting factor and inhibition of class VII learning motivation at SMPN 24 Jakarta. The method used quantitative research method with Post Test Only Control Group Design. Data that has been distributed is processed and processed using the Likert scale. The data analysis techniques used in this study are t test analysis and homogeneity test. The results of this study show that there is no significant difference in student learning motivation between classes and the use of application-based learning media, namely bandlabs with classes without the use of bandlab learning media. This is supported by research data on significance values of 0.856 > 0.05. The research was conducted online from their respective homes through online media Whatsapp and Zoom Meeting